Pro Android Media: Developing Graphics, Music, Video, and Rich Media Apps for Smartphones and Tablets - Every, Shawn Van (Apress, 2012)
In this chapter, we’ll look at the basics of image capture and storage on Android. We’ll explore the built-in capabilities that Android provides first and in later chapters move into more custom software. The built-in capabilities for image capture and storage provide a good introduction to the overall media capabilities on Android and pave the way toward what we’ll be doing in later chapters with audio and video. With that in mind, we’ll start with how to harness the built-in Camera application and move on to utilizing the MediaStore, the built-in media and metadata storage mechanism. Along the way, we’ll look at ways to reduce memory usage and leverage EXIF, the standard in the consumer electronics and image processing software worlds for sharing metadata.